Comparison of meat quality traits of scalded and non-scalded broiler breast meat - Iromi, T.; Shan Randima, N.; Sethukali, A.; Maleeka Nadeemale, N.; Amila, A.; Jung, M.H.; Dinesh Darshaka, J. (Animal Industry and Technology, 2021)
The objective of this study was to investigate the physicochemical and sensory attributes of scalded (SBC) and non-scalded (NSBC) broiler chicken breast meat. Ten carcasses from each type of chicken were randomly selected from the processing line of a commercial broiler processing plant. After dissecting the breast meat, physiochemical parameters such as pH, color, cooking loss, and proximate composition and sensory characteristics were examined. SBC contained higher protein but a lower fat content in breast meat compared to NSBC (p < 0.05). CIE L*, CIE a*, and CIE b* values of breast meat have not differed (p > 0.05) between NSBC and SBC. Higher pH values were shown by NSBC (p < 0.05) and no difference in cooking loss of breast meat from NSBC and SBC was observed (p > 0.05). Results of the sensory analysis showed a difference (p < 0.05) in the overall acceptability of breast meat between SBC and NSBC. Further studies are suggested to compare the levels of taste active compounds between SBC and NSBC.
Keywords: Breast meat; Broilers; Physicochemical; Scalding; Sensory